Substitution elasticities between capital, labour, material, electricity and fossil fuels in German producing and service sectors - Henrike Koschel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
In this paper, substitutional relationships between capital, labour, material, electricity, and fossil fuels in German producing and service sectors are estimated using a translog cost function. Estimates are based on a pooled time-series cross-sectional data sample for the period 1978-90 and nearly 50 sectors reported by the national account statistics. Results indicate that, except for the service sectors, own-price elasticities of all factor demands are below 0.5 (in absolute terms). In terms of the Morishima elasticity of substitution, labour and capital are substitutes in all sectors. Labour is generally a substitute for electricity, but not for fossil fuels. Results also support the hypothesis of capitalenergy substitutability and that the German economy is characterised by a nonhomothetic, non-constant-returns-to-scale production function. Substitution elasticities between input aggregates are estimated based on the nesting structure which underlies the computable general equilibrium model GEM-E3. Testing for weak homothetic separability restrictions, however, yields that input aggregation is allowed only in particular cases. Simulations with the GEM-E3 model demonstrate that the impacts of an ecological tax reform respond to a variation of substitution elasticities, but, all in all, the model proves to be relatively stable within a plausible range of values.
Keywords: 330; Faktorsubstitution; Substitutionselastizität; Kapital; Arbeit; Elektrizität; Fossiler Energieträger; Schätzung; Deutschland; Ökosteuer; Steuerwirkung; Allgemeines Gleichgewicht; Deutschland; Translog cost function